Biomarkers of malignancy in pleural effusions - José M. Porcel; Laura Porcel (Barcelona Respiratory Network Reviews)
The measurement of biomarkers in pleural fluid plays a crucial role in the diagnosis of malignant pleural effusion. Four types of biomarkers are discussed in this review: (1) soluble protein biomarkers, such as combined carcinoembryonic antigen and carbohydrate antigen 15-3, which can provide valuable insights into the malignant nature of an effusion, particularly those with false-negative cytology; (2) immunocytochemical biomarkers, which help establish the mesothelial, epithelial, or other cell origin of a malignant effusion, as well as the primary tumor invading the pleura (e.g., epithelial cell adhesion molecule and claudin-4 in carcinomas, or loss of BRCA1-associated protein 1 and methylthioadenosine phosphorylase in mesotheliomas); (3) flow cytometry biomarkers, which identify lymphoproliferative as well as epithelial neoplasms; and (4) molecular biomarkers (e.g., oncogenic or driver mutations), which phenotypically characterize a tumor and predict its response to target therapy or immunotherapy.